-2x-13+-8x+13=90

Simple and best practice solution for -2x-13+-8x+13=90 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2x-13+-8x+13=90 equation:


Simplifying
-2x + -13 + -8x + 13 = 90

Reorder the terms:
-13 + 13 + -2x + -8x = 90

Combine like terms: -13 + 13 = 0
0 + -2x + -8x = 90
-2x + -8x = 90

Combine like terms: -2x + -8x = -10x
-10x = 90

Solving
-10x = 90

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Divide each side by '-10'.
x = -9

Simplifying
x = -9

See similar equations:

| 6x+9=5x-12 | | 5d=5d+4 | | 16+6x=8y | | -9(x-6)-6=48 | | -y+2x=24 | | 4x=9x+54-2 | | -3+4f=10+4f | | K+2=5k+10 | | x+3y+4z=-4 | | 5a=2a+3 | | -3y-1=-1-3y | | 16+8x=8y | | 50-(3x+10)= | | -3+8-6t=-6t+5 | | -4-3x=-10-4k | | 3a-(8-6b)= | | -8-8m=-8m-8 | | 5+3x=8x+10 | | 7-(4y-1)=2-5y | | 3-5b=7-6b | | -8p=-4p-4p | | 8.6x+1.09=21.5x+16.9 | | 3(x+8)=-36 | | 4(3x+9)=-38+62 | | 3k+8=5k-8 | | 72=16t^2+4t | | 15x+3=10x+18 | | 2(3x-4)+3=21 | | 6-9r=-9r | | 11x-53=46 | | -4-3x=-5 | | 7x+3=6+5 |

Equations solver categories